SELF CARE MANAGEMENT IN DIABETES MELITUS SUFFERERS AT NGANJUK COMMUNITY HEALTH CENTER - Sony Wahyu Tri Cahyono (Journal for Research in Public Health, 2025)
Self-care management of diabetes is the basis for successful treatment of diabetes mellitus and plays an important role in achieving blood sugar control, reducing the risk of complications, improving quality of life and reducing the incidence of hospitalization. Several problems that arise in DM patients can be controlled if the patient can apply self-care management behavior to their disease. The aim of this research is to determine self-care management in diabetes mellitus sufferers at the Nganjuk Community Health Center. This research used a descriptive research design and this research was conducted at the Nganjuk Community Health Center. With the total population of diabetes mellitus sufferers at the Nganjuk Community Health Center being 55 people. With a sample of 53 respondents suffering from diabetes mellitus using accidental sampling technique. The variable of this research is Self Care Management in Diabetes Mellitus Patients. The research instrument used a questionnaire. The results of this study showed that of the 53 respondents, 41 respondents (77%) had good self- care management, 10 respondents (19%) had sufficient self- care management and 2 respondents (4%) had poor self-care management. Based on this research, almost all of them are in the good self-care management category. This is influenced by gender, age, education level, and length of time suffering from DM. Some of these factors, gender has an influence on the quality of self-care management, that is, women care more about their health status so they have good quality self-care management. It is hoped that diabetes mellitus sufferers can maintain self-care management to prevent complications.